Happiness in the Workplace of Women Lecturers Based on Work-Family Balance and Work Engagement - Nita Sri Handayani; Djamaludin Ancok; Dian Kemala Putri (Российский психологический журнал, 2023)
Introduction.  Happiness at work is one of the components that can determine the achievement of one's success at work. Lecturers are teaching staff at the tertiary level who are an important component of the education system. Lecturers who have happiness at work will have a higher work engagement with their work, have a high concentration in doing their work, are always enthusiastic in doing all their work, and are always enthusiastic in completing all their work. The purpose of this study was to theoretically test the variables of work-family balance and work engagement on the happiness of female lecturers.